2022
DOI: 10.1097/rlu.0000000000004203
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Limiting Bone Marrow Toxicities After Peptide Receptor Radionuclide Therapy Are More Prevalent in Women Than in Men

Abstract: PurposePeptide receptor radionuclide therapy (PRRT) can cause dose-limiting toxicities (DLTs) of the bone marrow, liver, and kidneys. It is yet unknown whether women and men are equally at risk of these DLTs.MethodsNeuroendocrine tumor patients treated with 177Lu-DOTATATE between 2000 and 2015 in our phase II trial with available laboratory data were included. For all DLTs, the highest Common Terminology Criteria for Adverse Events (version 4.03) grades that occurred from the start of PRRT until 3 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Svensson et al, using image-based dosimetry with both planar and SPECT/CT data, similarly found a significant absorbed dose correlation for platelets and WBC concentrations in 46 patients, while also reporting a significant correlation between absorbed dose and Hb concentration [ 12 ], while based on a different dosimetric approach, our study confirms those relationships, while also adding data on neutrophil granulocytes. The current results also align well with the observed trends in platelets and Hb reported by Minczeles et al [ 16 ]. The dataset of the presented study is larger than those previously published with dosimetric data and may therefore have higher statistical power to find any underlying dose–response relationships.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Svensson et al, using image-based dosimetry with both planar and SPECT/CT data, similarly found a significant absorbed dose correlation for platelets and WBC concentrations in 46 patients, while also reporting a significant correlation between absorbed dose and Hb concentration [ 12 ], while based on a different dosimetric approach, our study confirms those relationships, while also adding data on neutrophil granulocytes. The current results also align well with the observed trends in platelets and Hb reported by Minczeles et al [ 16 ]. The dataset of the presented study is larger than those previously published with dosimetric data and may therefore have higher statistical power to find any underlying dose–response relationships.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is not yet clear how such a scheme should best be devised. Skeletal metastases have been reported as a risk factor for bone marrow toxicity by others [ 10 , 13 , 16 ], but with some contradictory data [ 6 ], that reported no higher risk of subacute haematological toxicity in patients with skeletal metastases. Bodei et al have previously reported risk factors for long-term haematological toxicity, including initial thrombocytopenia and prior chemotherapy, which was not given to any patients in the current dataset [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased hair loss is observed in up to 60% of patients treated with 177 Lu-DOTATATE, but this is temporary and seldom leads to baldness [ 88 ]. Besides these mild adverse events, PRRT can induce more severe toxicities which can be dose-limiting and adjustments to the treatment schedule might be required [ 89 ]. When the toxicity has subsided within 16 weeks after the last dose, guidelines advise to administer half of the original activity of 177 Lu-DOTATATE during the next cycle.…”
Section: Prrt-related Toxicitymentioning
confidence: 99%
“…Known risk factors for severe hematological toxicity include decreased renal function, pre-existent cytopenias, extensive tumor mass, age over 70, extensive bone metastases and pre-treatment with myelotoxic chemotherapy [ 91 , 93 , 94 ]. Additionally, women are at higher risk for developing subacute grade ≥ 2 thrombocytopenia than men, which was independent from other risk factors in a multivariable analysis [ 89 ].…”
Section: Prrt-related Toxicitymentioning
confidence: 99%
“…Since the bone marrow is generally the dose-limiting organ in patients treated with PRRT with 177 Lu-DOTATATE, dose reductions should be considered in patients with high-volume bone metastases to prevent long-lasting cytopenia ( 35 , 36 , 64 ). At baseline, patients who are potential candidates for PRRT with 177 Lu-DOTATATE should have hemoglobin ≥ 5 mmol/L (8 g/dL); white blood count ≥ 2 × 10 9 /L; platelets ≥ 75 × 10 9 /L.…”
Section: Toxicity and Risksmentioning
confidence: 99%